Dolores después del Grito. Estrategias militares insurgentes y realistas en el norte de Guanajuato, 1810-1821 (Tzintzun, Revista de Estudios Históricos, 2016)
he main goal of the present paper is to study the military strategiesdrawn up by the insurgents and the royalists in the Congregación deDolores between 1810 and 1821. Between 1813 and 1814, the rebelsorganized military forces in Dolores with the aim of controlling miningin Guanajuato and thereby tried to dominate the towns and villagesof the bajío. Ater 1814, this population had the highest importancein the attempt to attack the southern part of the intendency of SanLuis Potosí and the so-called “barn of the New Spain”. Ater 1816, theroyalist governments established the so-called “General NorthernHeadquarters of the Guanajuato Province”, with its seat in Dolores,whose principal military goal was to bring complete peace to this partof the New Spain.
Keywords: Dolores Hidalgo; Guanajuato; independence process; royalists and insurgents; Bishopric of Michoacán; military historiography